Challenges and Prospects of Arabic in the Modern Era: Tantangan dan Prospek Bahasa Arab di Era Modern - Al Qolbi, Ahmad Syifa; Khan, Lubna Farah; Ulfiandi, Ihsan Zikri (Ma'arif Journal of Education, Madrasah Innovation and Aswaja Studies, 2024)
Arabic language education faces a number of challenges in the modern era that affect its future prospects. These challenges include linguistic, curricular, and sociological issues. However, by identifying and understanding these challenges, there are promising prospects for improving Arabic language education in the future. Efforts to integrate technology into learning, expand access to learning resources, improve the quality of teaching, and promote the importance of Arabic in a global context are steps that can be taken. Nevertheless, Arabic language education remains relevant and has important value, especially among Muslims. By continuing to adapt to the development of the times, Arabic will continue to have important and relevant values ​​throughout time.